2017
DOI: 10.1186/s13287-016-0467-0
|View full text |Cite
|
Sign up to set email alerts
|

GMP-conformant on-site manufacturing of a CD133+ stem cell product for cardiovascular regeneration

Abstract: BackgroundCD133+ stem cells represent a promising subpopulation for innovative cell-based therapies in cardiovascular regeneration. Several clinical trials have shown remarkable beneficial effects following their intramyocardial transplantation. Yet, the purification of CD133+ stem cells is typically performed in centralized clean room facilities using semi-automatic manufacturing processes based on magnetic cell sorting (MACS®). However, this requires time-consuming and cost-intensive logistics.MethodsCD133+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…In the present study, we have characterized the phenotype of both stem cells types. The flow cytometric strategy relied on our previous work [13,15]. Cultivated MSC are often characterized by the expression of several surface marker including CD73, CD105, and CD44 as well as the absence of others, including CD45 and CD34 [2,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we have characterized the phenotype of both stem cells types. The flow cytometric strategy relied on our previous work [13,15]. Cultivated MSC are often characterized by the expression of several surface marker including CD73, CD105, and CD44 as well as the absence of others, including CD45 and CD34 [2,13].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have examined whether CD133 + and CD271 + cells form separate populations within BM or if the surface proteins are also expressed simultaneously by an overlap population, which is an important aspect in order to evaluate the feasibility of a combined therapeutic approach. Taking into account that the majority of CD133 + cells express CD34 + , MACS-purified CD133 + cells were co-stained with CD34 antibody [14,15]. Moreover, the CD271 + population was co-stained for CD45 for further distinguishing of the MSC subpopulation lacking the CD45 surface marker [16].…”
Section: Flow Cytometric Characterization Of Stem Cell Populations Qmentioning
confidence: 99%
“…Some have been defined as pro-arrhythmogenic cells, i.e., skeletal myoblasts, while others have shown antiarrhythmic effects, such as embryonic cardiomyocytes and mesenchymal stem cells (MSC) [2][3][4][5]. Our research group has focused on the role of human bone marrow (BM) derived hematopoiesis such as MSC in regenerative medicine [6][7][8][9]. In previous studies we have shown that it is safe to use CD117 + stem cells for myocardial regeneration, as their electrophysiological properties…”
Section: Introductionmentioning
confidence: 99%
“…With numbers of 10 9 MSC, effects were reported in treatment of some autoimmune and infectious diseases [68,69]. A lot of clinical trials have been performed or are ongoing on treating cardiovascular diseases (myocardial infarction, cardiomyopathy, critical limb ischemia, stroke [72][73][74]). Single or repeated doses of 10 7 to more than 10 9 are injected systemically or topically.…”
Section: State-of-the-art With Ex Vivo Expanded Mscs Utilized In Clinmentioning
confidence: 99%